Posthypertonic Lysis of Human Erythrocytes in Chlorpromazine Presence - Semionova, Ekaterina A.; Ershova, Nataliya A. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):182.